A Proposed Method for Fruit Grading from Fruit Images using SVM - Banerjee, Priyanka; Sur, Souvik; Dey, Kashi Nath; Bandyopadhyay, Samir Kumar (International Journal of Computer Sciences and Engineering, 2020)
Agriculture is the largest economic sector and it plays a major role in economic development of India. The manual classification and grading techniques of fruits are distinguished between different types of fruits. Many new technologies are developed by researchers but enhance method is still needed. This paper presents a method for fruit grading from fruit images using image processing and machine learning techniques.